2016
DOI: 10.1002/dmrr.2808
|View full text |Cite
|
Sign up to set email alerts
|

Significant inverse association between serum osteocalcin and incident type 2 diabetes in a middle‐aged cohort

Abstract: Background Accumulating evidence indicates that osteocalcin links bone formation to glucose homeostasis. However, the correlation between osteocalcin and incident type 2 diabetes has been controversial based on the limited results of cohort studies. We examined the link between serum osteocalcin and glucose homeostasis including incident type 2 diabetes in a 3-year follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(53 reference statements)
3
15
0
Order By: Relevance
“…These findings are in accordance with previous results showing that N-MID was protective against T2DM by improving insulin sensitivity and secretion. Furthermore, the same role of osteocalcin in glucose metabolism was also demonstrated in previous population studies [19,26,27] . Therefore, osteocalcin is a critical molecule that favorably modulates glucose homeostasis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are in accordance with previous results showing that N-MID was protective against T2DM by improving insulin sensitivity and secretion. Furthermore, the same role of osteocalcin in glucose metabolism was also demonstrated in previous population studies [19,26,27] . Therefore, osteocalcin is a critical molecule that favorably modulates glucose homeostasis.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the intermittent infusion of osteocalcin was shown to partially correct the glucose intolerance caused by a high-fat diet in mice [15] . Although animal studies have provided evidence supporting a key role for bone in energy metabolism via osteocalcin, the association between osteocalcin and glucose metabolism remains controversial based on previous observational studies in humans [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…In a large cross-sectional analysis of older men aged 70 to 89 years residing in the community of Perth, Western Australia, higher ucOC was found inversely associated with reduced diabetic risk [25]. Shu et al found OC at baseline was negatively related to the risk of incident T2DM during a 3-year follow-up [26]. In addition, maternal oral administration of ucOC during gestation protected high-fat, high-sucrose diet-fed female offspring from metabolic disorders induced by maternal obesity [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis assessing the association between OCN and T2DM, higher serum OCN was associated with a lower incidence of T2DM in cross‐sectional studies, whereas in cohort trials, the risk of T2DM was only marginally decreased in individuals with higher serum OCN . Several large‐scale human studies from Japan and China demonstrated that a lower baseline serum OCN level, for example, less than 6 ng/mL, was associated with increased risk of future development of T2DM and prediabetes . Thus, the predictive value of OCN with respect to incident dysglycaemia and diabetes should be further tested and verified in different ethnic populations …”
Section: Osteoblast‐derived Ocn As An Insulin Secretagogue and Insulimentioning
confidence: 99%
“…52 Several large-scale human studies from Japan and China demonstrated that a lower baseline serum OCN level, for example, less than 6 ng/mL, was associated with increased risk of future development of T2DM and prediabetes. [53][54][55] Thus, the predictive value of OCN with respect to incident dysglycaemia and diabetes should be further tested and verified in different ethnic populations. 47 It should be noted that only ucOC has metabolically active functions in mouse studies 6 and that the γ-carboxyglutamate (Gla) residuals of OCN differ between mice and humans.…”
Section: Osteoblast-derived Ocn As An Insulin Secretagogue and Insumentioning
confidence: 99%